Tricuspid Valve Hemangioma Associated with Hypoplastic Left Heart Syndrome Presenting as Sudden Infant Death Syndrome - Brijnandan GUPTA; Shouriyo GHOSH; Maikal KUJUR; Khushbu KHETAN; Tarun KUMAR (Federation of Turkish Pathology Societies, 2019)
Primary cardiac tumors are rare in children with a low incidence varying from 0.0017 to 0.28% in autopsy studies. Approximately 90% of the reported primary cardiac tumors in the pediatric population are benign and the most common subtype is rhabdomyomas accounting for approximately 60%, while hemangiomas are rare primary tumors with a 5% incidence. Hypoplastic left heart syndrome is abnormal development of the left-sided cardiac structures, leading to obstruction of blood flow from the left ventricle out-flow tract. Here we report a case of tricuspid hemangioma in association with hypoplastic left heart syndrome, a rare association not previously reported in the literature.